2010
DOI: 10.1089/met.2009.0062
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Diabetes in South Asian Indians in the United States: Findings From the Metabolic Syndrome and Atherosclerosis in South Asians Living in America Study and the Multi-Ethnic Study of Atherosclerosis

Abstract: Background: Individuals from South Asia have high diabetes prevalence despite low body weight. We compared the prevalence of diabetes among South Asian Indians with other U.S. ethnic groups and explored correlates of diabetes. Methods: This was a cross-sectional study of 150 South Asian Indians (ages 45-79) in California, using similar methods to the Multi-Ethnic Study of Atherosclerosis (MESA). Type 2 diabetes was classifi ed by fasting plasma glucose (FPG) ≥126 mg/dL, 2-h postchallenge glucose ≥200 mg/dL, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
105
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(109 citation statements)
references
References 38 publications
2
105
2
Order By: Relevance
“…8 Therefore, we examined the relationships between endogenous sex hormone levels and lipoprotein subclasses using data from preliminary studies of the MASALA study, a cohort of Asian Indians in the United States. 9 The aim of this secondary analysis was to determine whether more androgenic profiles were associated with more atherogenic lipoprotein subfraction profiles in women and less atherogenic lipoprotein profiles in men and whether such associations persisted after consideration of adipose tissue mass.…”
Section: Introductionmentioning
confidence: 99%
“…8 Therefore, we examined the relationships between endogenous sex hormone levels and lipoprotein subclasses using data from preliminary studies of the MASALA study, a cohort of Asian Indians in the United States. 9 The aim of this secondary analysis was to determine whether more androgenic profiles were associated with more atherogenic lipoprotein subfraction profiles in women and less atherogenic lipoprotein profiles in men and whether such associations persisted after consideration of adipose tissue mass.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that risk factors for T2D increase following immigration; however, in South Asian immigrants settled in United States (Kanaya et al, 2010), the prevalence of T2D was decreased. In a study of Middle-eastern immigrants settled in Sweden (Glans et al, 2008), the authors found an earlier onset of diagnosis of T2D, a stronger family history and a more rapid decline of pancreatic B-cell function than in Swedish patients.…”
Section: Risk Of Hospitalization For Type 2 Diabetes In First-and Secmentioning
confidence: 86%
“…We selected the parameters from the results of baseline measurements that we communicated to the participants. We calculated BMI as weight (kg)/height (m) 2 . We classified blood test results on the basis of the fasting and 2-h post-load glucose values from the OGTT, the HbA1c value and the HOMA-IR.…”
Section: Potential Confounders and Effect Modifiersmentioning
confidence: 99%